The Correlation between Village Funds, Village Fund Allocation, and Gender in Village Development - Wulan Nur Anggraeni; Muhammad Asim Asy’ari (Jurnal Ragam Pengabdian, 2026)
This study aims to determine the relationship between village fund, allocation of village fund and gender with village development. This type of research uses quantitative research. The population in this study is the scope of village government in Bangkalan Regency during the period 2018-2020. The sampling technique used non-probability sampling method with purposive sampling. The data used in this research uses secondary data. Data collection techniques were obtained from the Bangkalan Regency DPMD Office and the official website. The data analysis technique used the pearson correlation test using SPSS 21.0. Based on the results of the pearson correlation research, it shows that: village funds, allocation of village fund and gender have a relationship with village development. However, the level of the relationship both has a very weak level of correlation.